Consolidating Human Capital Advantage For Sustainability And Competitiveness - Godbless, Eromafuru Edward (Archives of Business Research, 2018)
The 21st century managers must sit up and be alert to unprecedented changes that have implications for their corporate identity and future existence. To survive, they should no longer wait for the wind of change to blow away their organizations. They must be ready at all times to act promptly for the sustenance of their organizations. Never has the world of mankind been so slippery, precarious, diversified, hostile, dynamic and futile. Increasing government interventions and expectations for quality products and service, corporate resistance to change and swift technological change have added to the complexity and awesome of today’s business environments. Converting the above threat into own advantage puts heavy pressures on today’s managers to develop and consolidate on latent skills which organizations need for survival. In this article, the writer holistically examines the concept of human capital and its facets with a prognosis of how its philosophies, principles, strategies and practices can be adapted to meeting the developmental needs of Nigerian firms in the present-day competitively-driven business world.